Peningkatan Kemampuan Kognitif Anak Usia 5 – 6 Tahun Melalui Penerapan Permainan Sains di PAUD Eklesia Sabkiki Desa Nule Kabupaten Timor Tengah Selatan - Jenny Yutje Oematan (Institut Nalanda, 2024)
This research aims to improve the cognitive abilities of children aged 5-6 years through the application of science games. This research is Classroom Action Research (PTK) which consists of two cycles. Each cycle has three meetings and four stages are carried out, namely planning, implementing actions, observing and reflecting. The subjects of this research were children aged 5-6 years at Eklesia Sabkiki PAUD, Nule Village, South Central Timor Regency, 2021/2022 Academic Year, with a total of 15 children. Data collection techniques use observation data, interviews, tests and documentation. Data analysis in this research uses quantitative data analysis and qualitative data analysis, namely interactive data analysis. The results of this classroom action research show an increase in children's cognitive abilities in each cycle. The percentage of pre-action completion was 33.33% with 5 children completing it. In cycle I it increased with a percentage of 60% or 9 children who completed, and in cycle II with a percentage of 80% or 12 children who completed. Based on the results of classroom action research carried out in two cycles, it can be concluded that through the application of science games, it can improve the cognitive abilities of children aged 5-6 years in Eklesia Sabkiki PAUD students, Nule Village, District. South Central Timor 2021/2022 Academic Year